Paracetamol poisoning and level of knowledge on protocol of use of N-Acetylcysteine (NAC) as its antidote among pharmacy staffs in Hospital Tengku Ampuan Afzan (HTAA) - Abu Bakar, Nurul Nabilah; Mamat, Kamal Azrin (2013)
This study focuses on statistic of Paracetamol poisoning or toxicity and the level of knowledge on protocol of use N-acetylcysteine (NAC) among pharmacy staffs. This study was done at Hospital Tengku Ampuan Afzan (HTAA), Kuantan, Pahang which also own a Therapeutic Drug Monitoring unit. The pharmacy staffs at Hospital Tengku Ampuan Afzan were our study subject. To evaluate the level of knowledge on protocol of use NAC, we distributed a set of questionnaire for them to answer. The focus of this project is to study the relationship between their demographic factors which are designation, department, gender, age, work experience and experience in handling Paracetamol toxicity cases with the level of knowledge on protocol of use on NAC. For the statistic of Paracetamol toxicity, we collected the data by tracing the records kept in Therapeutic Drug Monitoring unit throughout the year of 2012 . To analyze the data from 40 filled questionnaires we manage to collect, Microsoft Excel 2007 is used for data and graphing presentation. From the data we know that most of them (52.5%) have low level of knowledge on protocol of use NAC in Paracetamol poisoning. The result of this study can be used by HTAA to gain information on the statistic of Paracetamol suspected toxicity in 2012 and expose the pharmacy staffs to the use of NAC protocol.